Návrh rozvoje systému hodnocení a odměňování zaměstnanců ve vybrané společnosti - Vávra, Radovan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce se zabývá problematikou hodnocení a odměňování zaměstnanců ve vybrané společnosti. Práce je rozdělena na čtyři části. První část obsahuje teoretické poznatky týkající se dané problematiky. V další části je analyzován současný stav společnosti, kde je zahrnuta analýza systému hodnocení a odměňování zaměstnanců. Třetí část je věnována zaměstnaneckému průzkumu a řízenému rozhovoru s vedoucím výrobního segmentu. V poslední části práce jsou návrhy na další rozvoj systému hodnocení a odměňování zaměstnanců.

The diploma thesis deals with the proposal for change to the system of evaluation and remuneration of employee in the selected company. The thesis is devided into four parts.The first part describes the basic concepts of the theoretical systems of the evaluation and remuneration of employee. The next part is analysis the current situation of the company, which includes an analysis of the system of evaluation and renumeration of employees. The third part is devoted to employee research and a guided interview with the head of the production segment. In the last part of this work are proposals for further development of the system of evaluation and remuneration of employees.
Proposal of development of system of evaluation and remuneration of employees in selected company
Keywords: Zaměstnanci; hodnocení a odměňování zaměstnanců; zpětná vazba; kompetenční model; zaměstnanecké výhody; tarifní třídy.; Employees; evaluation and remuneration of employees; feedback; competency model; employee benefits; tariff class.